Analysis of Rigid Pavement Using the Bina Marga and PCI Methods (Case Study: Jalan Lanud Sukani STA 1+500 – STA 4+500) - Teguh Puji Setiawan; Muhamad Taufik (LEADER: Civil Engineering and Architecture Journal, 2025)
As a developing country, Indonesia requires quality roads and adequate quantities to meet the needs of the community in carrying out various economic activities, both in terms of accessibility and the movement of goods and services. Accurate evaluation can identify types of damage such as cracks, potholes, or other deformations that can affect road performance. Routine maintenance may include filling cracks and repairing potholes, while periodic maintenance can involve resurfacing or partial reconstruction. The aim of this study is to determine the types of surface damage on Jalan Lanud Sukani STA 1+500 – STA 4+500. Data sources were obtained from primary data through surveys and secondary data. Data collection was conducted in November-December 2024. The research analysis used the Bina Marga (BM) method and the Pavement Condition Index (PCI) method.The results of the study using the Bina Marga method showed a priority value of 3. Meanwhile, the PCI method yielded a result of 16, which is classified as very poor. Therefore, the road condition value based on the PCI method is 8.